2020
DOI: 10.1039/d0cc04013d
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid–base synergistic catalysis of cationic halogen-bonding-donors with nucleophilic counter anions

Abstract: Cationic halogen-bonding-donors with little or non-coordinating counter anions have attracted great attention as new Lewis acid type organocatalysts. However, these anions cannot function as nucleophilic activation sites due to their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…There is only one reported example of a type-B compound (i.e., 1,2-dimethyl-3-iodoindazoium iodide), and its potential applications have not yet been explored. The triazoliums E 33,34,36,58,59 and H 37 were successfully utilized as organocatalysts, but no articles describe the preparation and application of compounds F, G, I, or J. The iodine-containing tetrazoliums K-N are also generally unexplored, and only one example of such compounds (i.e., 5-iodo-1,3-diphenyltetrazolium tetrafluoroborate; type K) has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one reported example of a type-B compound (i.e., 1,2-dimethyl-3-iodoindazoium iodide), and its potential applications have not yet been explored. The triazoliums E 33,34,36,58,59 and H 37 were successfully utilized as organocatalysts, but no articles describe the preparation and application of compounds F, G, I, or J. The iodine-containing tetrazoliums K-N are also generally unexplored, and only one example of such compounds (i.e., 5-iodo-1,3-diphenyltetrazolium tetrafluoroborate; type K) has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that 2-iodoimidazolium 10,30-32 and 4-iodo-1,2,3-triazolium 10,[33][34][35][36] salts effectively catalyze an extensive series of organic transformations, including (aza)-Diels-Alder cycloadditions, Michael additions, halide abstractions, olefin reductions, and many other reactions. 10 It is worth mentioning that one report also describes the preparation of 5-iodo-1,2,4-triazolium salts and presents their catalytic activity for Michael additions.…”
Section: Introductionmentioning
confidence: 99%
“…Deprotonative iodination also successfully provided ptrifluoromethylphenyl substituted iodotriazolium salt 4 ja, which was previously reported to exhibit excellent catalytic activity for the cyanosilylation of aldehydes. [10] When chlorodiphenylphosphine was used as an electrophile in the deprotonative functionalization, triazolium salt 5 aa bearing a diphenylphosphino group was not obtained with a complete recovery of 3 aa. The reason for this failure was most likely due to the consumption of potassium tert-butoxide by its nucleophilic attack toward chlorodiphenylphosphine.…”
Section: Entrymentioning
confidence: 99%
“…Typically, DFT calculation studies by Huber and co‐workers in 2017 verified the transition state of the Michael reaction catalyzed by the C−I moiety of the XBD catalyst, indicating that halogen bonding activated the oxygen of the carbonyl [32] . To our best knowledge, halogen bonding has not been exploited in CO 2 fixation [33] …”
Section: Introductionmentioning
confidence: 99%
“…[32] To our best knowledge, halogen bonding has not been exploited in CO 2 fixation. [33] CCE reactions were well promoted by hydrogen-bonding catalysis. Both binary [34] (Scheme 1a) and one-component [35] (Scheme 1b) H-bonding organocatalysts were designed, in which the H-bond donor activated the epoxide and the nucleophilic anion, usually a halide anion accompanied by an onium counterion, attacked the methylene carbon to trigger the ring-opening of the epoxide.…”
Section: Introductionmentioning
confidence: 99%